1988
DOI: 10.1007/bf00417269
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in the relationship of performance in the handgrip and standing long jump tests to lean limb volume in young adults

Abstract: Groups of young, adult males and females performed the handgrip and standing long jump tests. Their total forearm and leg volumes were calculated from a series of circumference and length measurements, and the lean volumes (bone + muscle) calculated by taking the skinfold thickness into consideration. In the handgrip, the mean female performance was 298 N compared with 496 N for the males. In the standing long jump, mean performance expressed as distance x body mass was 87.3 kg.m for females compared with 137.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 19 publications
1
26
0
2
Order By: Relevance
“…They reported a significant correlation coefficient between grip strength and back strength of r=0.501 and between grip strength and quadriceps strength of r=0.536. Additionally, three studies reported a significant correlation between grip strength and arm circumference and arm strength [15,28,30] and two studies reported a significant correlation between grip strength and jumping strength [9,16]. Also, several studies reported a significant association between grip strength and physical fitness or health status [1,7,22,36,40].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…They reported a significant correlation coefficient between grip strength and back strength of r=0.501 and between grip strength and quadriceps strength of r=0.536. Additionally, three studies reported a significant correlation between grip strength and arm circumference and arm strength [15,28,30] and two studies reported a significant correlation between grip strength and jumping strength [9,16]. Also, several studies reported a significant association between grip strength and physical fitness or health status [1,7,22,36,40].…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, muscle strength is an important outcome. However, muscle strength changes with growth, and therefore, values obtained in healthy children should serve as a reference for children and adolescents with acute and chronic conditions when muscle strength is a measure for diagnostic purposes, followup, or to assess the efficacy of therapy [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the anaerobic power diVerence between the sexes, one study accounted for the sex diVerence by anthropometric determination (Bruyn-Prevost and Sturbois 1984), while other studies failed to account for this (Davies et al 1988;Mayhew and Salm 1990;Nindl et al 1995). However, no study has reported on contributing factors to multiplanar explosive power using a side medicine-ball throw for male and female athletes.…”
Section: Introductionmentioning
confidence: 95%
“…Thickness of the stratum corneum of the volar fingertips has been found to be thinner in women than in men (Fruhstorfer et al 2000) and a significant difference between genders has been reported in collagen and elastic fibre density in 45 skin biopsies taken from limbs or the trunk (VitellaroZuccarello et al 1994). Tur (1997) summarised the differences in skin physiology between men and women: Skin thickness in young subjects (27-31 years) is greater in men than in women across the entire body except for the lower back (Seidenari et al 1994); Skinfold thickness in younger subjects (17-24 years) is lower in the limbs of women (Davies et al 1988) and skinfold compression is less in the limbs of women in younger subjects (Hattori et al 1993). …”
Section: Introductionmentioning
confidence: 99%